Familiarity matters: A review on prioritized processing of personally familiar faces. Issue 3 (16th March 2018) - Ramon, Meike; Gobbini, Maria Ida
ABSTRACT: In this review, we synthesize the existing literature investigating personally familiar face processing and highlight the remarkable, enhanced processing efficiency resulting from real-life experience. Highly learned identity-specific visual and semantic information associated with personally familiar face representations facilitates detection, recognition of identity and social cues, and activation of person knowledge. These optimizations afford qualitatively different processing of personally familiar as compared to unfamiliar faces, which manifests on both the behavioural and neural level.